Analisis Genetic Gain Ikan Nila Kunti (Oreochromis niloticus) Antara Generasi F4 Dan F5 Pada Umur 5 Bulan - Nugroho, Faried; Basuki, Fajar (Journal of Aquaculture Management and Technology, 2013)
Tilapia (Oreochromis niloticus) is one kind of freshwater fish which are economical important and widely cultivated by people as export commodities. The efforts to improve the quality of tilapia using selection program are needed in order to increase production and profitability of tilapia growers. High quality parents and seeds are absolutely necessary in tilapia farming activities because the superior parent seed quality is expected to be obtained as well. This study aims to compare the growth between Kunti Tilapia F4 males with F5 male and F4 female with F5 female and also to know the value of genetic gain Kunti Tilapia at age 5 months. Tested fish used in the study were Kunti Tilapia F4 and F5 at the age of 4 months. The rearing treatment lasted in 30 days. The variables measured were survival rate, relative growth rate, weight, total length, thickness, food convertion ratio, and genetic gain. This study used two treatments and 3 replications for each gender (F4 and F5 ♂ and F4 and F5 ♀). The research was conducted in October to November in SATKER PBIAT Janti, Klaten.The genetic gain value of Kunti tilapia from F4 to F5 generation at the age of 5 months are as follows, SR genetic gain : male (♂)2,72 % and female (♀)3,02 %; RGR genetic gain : male (♂) 11,37 % and female (♀) 10,78 %; weight genetic gain : male (♂)25,91 % and female (♀)24,9 %; total length genetic gain : male (♂) 8,08 % and female (♀) 1,51 %; thickness genetic gain : male (♂) 12,09 % and females (♀) 11,79 %; food convertion ratio (FCR) genetic gain : male (♂) 0,95 % and females (♀) 0,83 %. The Growth of Kunti Tilapia F5 generation is better than the F4 generation.